Dual targeting of EGFR and glutaminase in lung cancer. (4th May 2018) - Momcilovic, Milica; Shackelford, David B.
ABSTRACT: We have recently demonstrated that targeted inhibition of epidermal growth factor receptor (EGFR) signaling and glutaminase led to metabolic crisis in EGFR mutant lung adenocarcinomas and significant tumor regression in mouse xenograft models. Combining targeted therapies that restrict the metabolic activity and growth of tumors represents a therapeutic strategy that holds promise for clinical translation.